The influence of static and dynamic warm-up on knee temperature: infrared thermography insights before and after a change of direction exercise - Trovato, Bruno; Sortino, Martina; Petrigna, Luca; Roggio, Federico; Musumeci, Giuseppe (Frontiers in Physiology, 2024)
Introduction Infrared thermography is spreading in the field of sports medicine and performance. This study investigated the effects of static and dynamic warm-ups and a 90° change of direction exercise (COD) on the thermal response of the knee. Methods Thermograms were collected using the FlirE54 from 85 healthy young adults, 46 males and 39 females, aged 20 to 31 years old. Participants were divided in two groups, static and dynamic warm-up. Four thermograms were taken: baseline (T0), warm-up (T1), COD (T2), and rest (T3). Four regions of interest (ROI) of the knee were analyzed: anterior upper half (AUH), anterior lower half (ALH), posterior upper half (PUH), and posterior lower half (PLH). Mixed ANOVA with the Bonferroni-Holm test and independent t-test were used, respectively, for pairwise comparison and to spot differences between the right and left knee at T1 and T2 and at T0 between males and females. Results The mixed ANOVA was significant for time points (p<0.001) in all the ROI, and for stretching/temperature interaction with different levels of significance. The t-test for the right and left knee at T1 and T2 resulted not significant. The temperature in the static warm-up group followed a decrease at T1, a subsequent drop at T2 and a recovery similar to baseline at T3, in the ALH in males and females and in the PUH only in males. Conclusions The static stretching was more suitable in preparing the knee for the COD exercise compared to the dynamic one in terms of thermal response.